2022
DOI: 10.1186/s12936-022-04135-4
|View full text |Cite
|
Sign up to set email alerts
|

Using the Ghana malaria indicator survey to understand the difference between female and male-headed households and their prevention and testing for malaria among children under 5

Abstract: Background Globally, 94% of malaria deaths occur in sub-Saharan Africa, and children under age 5 account for 70% of malaria-related mortality in the region. This study sought to examine differences between female-headed households (FHHs) and male-headed households (MHHs) with regard to malaria prevention and testing among children under age 5 (U5) in Ghana. Methods This cross-sectional study used publicly available data from the 2019 Ghana Malaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This is meant to illustrate how gender roles affect how households control malaria. Recently, it has been argued that female-headed families are more likely to report adopting preventative measures against malaria, such as dousing the home in pesticide, draining stagnant puddles, and maintaining a clear environment [ 26 ]. However, this may not always be true.…”
Section: Resultsmentioning
confidence: 99%
“…This is meant to illustrate how gender roles affect how households control malaria. Recently, it has been argued that female-headed families are more likely to report adopting preventative measures against malaria, such as dousing the home in pesticide, draining stagnant puddles, and maintaining a clear environment [ 26 ]. However, this may not always be true.…”
Section: Resultsmentioning
confidence: 99%
“…Barry et al [ 44 ] found a link between head of household and malaria preventive measures among pregnant women in Guinea. A Ghanaian study found that homes that were headed by males were more likely to own ITN [ 45 ]. As a result, health workers should strengthen partner involvement in ANC activities as this can help drive home preventive education on malaria, such as ITN use.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Sub-Saharan Africa (SSA) accounted for 94% of global malaria deaths. Furthermore, children under the age of five (U5) accounted for 70% of malaria-related mortality in the SSA region 2 , 3 . An increase to 96% of malaria-related death is recorded in WHO African Region in 2021, and the top 16 malaria-affected countries are all situated in SSA.…”
Section: Introductionmentioning
confidence: 99%